A method to determine the orientation of the upper arm about its longitudinal axis during dynamic motions - Gordon, B. J.; Dapena, J. (Journal of Biomechanics, 2013)
Inaccuracy in determining the orientation of the upper arm about its longitudinal axis (twist orientation) has been a pervasive problem in sport biomechanics research. The purpose of this study was to develop a method to improve the calculation of the upper arm twist orientation in dynamic sports activities. The twist orientation of the upper arm is defined by the orientation of its mediolateral axis. The basis for the new method is that at any angle in the flexion/extension range of an individual`s elbow, it is possible to define a true mediolateral axis and also a surrogate mediolateral axis perpendicular to the plane containing the shoulder, elbow and wrist joints. The difference between the twist orientations indicated by these two versions of the mediolateral axis will vary from one elbow angle to another, but if the elbow joint deforms equally in different activities, for any given subject the difference should be constant at any given value of the elbow angle. Application of the new method required individuals to execute sedate elbow extension trials prior to the dynamic trials. Three-dimensional motion analysis of the sedate extension trials allowed quantification of the difference between the true and surrogate mediolateral axes for all angles in the entire flexion/extension range of an individual`s elbow. This made it possible to calculate in any dynamic trial the twist orientation defined by the true mediolateral axis from the twist orientation defined by the surrogate mediolateral axis. The method was tested on a wooden model of the arm.